MENINGKATKAN MINAT BELAJAR PKn PADA MATERI PERSAMAAN KEDUDUKAN WARGA NEGARA DENGAN MENERAPKAN MODEL STUDENT TEAMS-ACHIEVENT DIVISION (STAD) DI KELAS X4 SMA NEGERI 12 BANJARMASIN - Baihaki Baihaki (Jurnal Pendidikan Kewarganegaraan, 2014)
Baihaki, 2013. Improving to interests in Learning Civics of material citizen status Equation Approach With Applying Student Teams Achievement Division (STAD) in Class X-4 SMAN 12 Banjarmasin. thesis, program Study of citizenship and pancasila education department of social siences education, faculty of teacher and education science, university of lambung mangkurat. Counselor  (1) Acep Supriyadi (2) Dian Agus Ruchliyadi.During this learning process Civics in class X-4 SMAN 12 Banjarmasin likely not achieve results as expected. It is seen from the students who are interested in the subject PKN brackets, so that the students' learning outcomes is low.Research objectives are: (1) To determine whether the application of the model Student Teams-Achievement Division (STAD) can be improving the students' interest in civics lesson. (2) To determine the level of students' interest in learning after using Civics model of Student Teams-Achievement Division (STAD) in the Class X-4 SMAN 12 Banjarmasin. (3) To determine student learning outcomes after using model of Student Teams-Achievement Division (STAD) in class X-4 SMAN 12 Banjarmasin. Data collection techniques used are observation, documentation and test results of learning is done through several cycles, the first cycle and second cycle. The results showed (1) the percentage of students' interest towards learning Civics using STAD cooperative learning models known to the majority of students answered "yes", with the median percentage of student interest is 74% or better are included in the qualification. (2) The interest of the students for learning is also getting better, in the first cycle is only 60% interest students performed better after the second cycle increased to 78%. (3) except that the most important thing is to improve student learning outcomes Civics mastery learning where improvement can be seen in the achievement of minimal classical completeness that the first cycle is low with 28% percentage of pretest and post-test 40%, after following for reflection on the learning cycle both gain increased mastery results with 84% percentage of pretest and post-test by 92%. Implementation of the study until completion is supported by many factors such as the availability of support facilities and infrastructure while also inhibiting factors that are still unfamiliar students using this learning model, expected later after the implementation of this model will appear model new learning model is more attractive and easier for students to understand that learning results according to the criteria of completeness maximum graduation (KKM). Student interest in following subjects will increase with applied models are attractive because students was not bored and tired in the course. Later the teacher should always provide motivation for students are always interested in the following lesson.keywords: Increasing to Interest in Learning Civics, Approach (STAD)